Exploring inflow wind condition on floating offshore wind turbine aerodynamic characterisation and platform motion prediction using blade resolved CFD simulation. (January 2022) - Zhou, Yang; Xiao, Qing; Liu, Yuanchuan; Incecik, Atilla; Peyrard, Christophe; Wan, Decheng; Pan, Guang; Li, Sunwei
Abstract: The present study is aimed at investigating the effect of turbulent wind and shear wind on the floating offshore wind turbine (FOWT) structure by using a high-fidelity computational fluid dynamics (CFD) method. This method is believed to resolve the wind field around the turbine blades, wake and the near air-wave free-surface regime, allowing us to have a more in-depth examination into both aerodynamic and hydrodynamic of the FOWT. In the present study, the modelling of a coupled aero-hydro-mooring FOWT system is focused on a temporal and spatial variable turbulent wind field by using a time-varying spectrum, which has not been examined for a floating wind turbine. The turbulent wind in the study is generated with Mann's wind turbulence model, while the Von Karman wind spectrum is used to represent wind turbulence. In addition, different wind shears were also examined. We can conclude from this study that, when turbulent wind is present, there are fluctuations in both the rotor thrust and power outputs associated with the non-uniform wake region although the time-mean magnitude is almost the same. In addition, turbulence wind lead to a quicker wake diffusion than time-independent inflow wind. Furthermore, the existence of wind shear results in an even larger decrease in the local minimum thrust/power about 2–6% when the turbine blade is passing in front of the tower. Despite this, under the present wind inflow conditions, the inline surge force, dynamic motion, and the mooring tension of the floater are not significantly affected by either the turbulence wind or the wind shear.